2015
DOI: 10.1002/er.3345
|View full text |Cite
|
Sign up to set email alerts
|

Study of a Stirling engine used for domestic micro-cogeneration. Thermodynamic analysis and experiment

Abstract: SUMMARYOne of the aims of this work is the study of the geometry of a micro-cogenerator using a Stirling engine with four double effect pistons. The complex geometry of the heat exchangers was determined by optical measurements. Results of three thermodynamic models: Direct Method from Finite Speed Thermodynamics (FST), isothermal model (Schmidt), and adiabatic model (Finkelstein) are confronted to experimental ones. Direct Method consists of the study and the evaluation of the irreversibilities of thermal mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Among these cities, Tabriz had the highest overall efficiency and Bandar Abbas had better performance in the annual Stirling engine efficiency, the annual primary energy saving and annual carbon dioxide emissions reduction [107]. Grosu et al [108] presented a micro-CHP system with Stirling engine, and the results showed that the direct method and the adiabatic model had good accuracy. Ferreira et al [109,110] optimized a micro-CHP with a parabolic collector and a solar Stirling engine to produce heat and power.…”
Section: Parabolic Dish Collectorsmentioning
confidence: 99%
“…Among these cities, Tabriz had the highest overall efficiency and Bandar Abbas had better performance in the annual Stirling engine efficiency, the annual primary energy saving and annual carbon dioxide emissions reduction [107]. Grosu et al [108] presented a micro-CHP system with Stirling engine, and the results showed that the direct method and the adiabatic model had good accuracy. Ferreira et al [109,110] optimized a micro-CHP with a parabolic collector and a solar Stirling engine to produce heat and power.…”
Section: Parabolic Dish Collectorsmentioning
confidence: 99%
“…f eg is the output force of the PMLG and is related to the load coefficient C and the piston speed feg=Ctrueẋ(),t; f f is the mechanical friction force. (For more details about this model, please refer to Jia et al, Smallbone et al, Yuan et al, and Grosu et al)…”
Section: Pmlg Focused On Microgenerationmentioning
confidence: 99%
“…Features as compactness, cost efficiency, noiselessness, ease of installation, and low maintenance are required when cogeneration systems are considered for domestic applications [7]. Owing to the rising interest in this topic in the residential sector, current research can be found in the literature [8][9][10][11][12][13][14][15][16]. The facility presented in this investigation combines the conventional cogeneration scheme with a heat pump, creating an autonomous micro-cogeneration system.…”
Section: Introductionmentioning
confidence: 99%